ECONOMIC EMPOWERMENT OF INDIGENOUS COMMUNITIES THROUGH THE GAZETTEMENT OF LAND OWNERSHIP - Mohd Khori, Hairulnizam; Amat Simin, Mohamad Hafis; Ibrahim, Mohamad Asmawi; Sahadom, Muhammad Nur Iman; Lokman, Atikah (PLANNING MALAYSIA, 2024)
Most of Malaysia's indigeneous (Orang Asli) population continues to live according to traditional customs, especially when it comes to business. The subsistence farming practices and natural resources are the main sources of income for the Orang Asli community in Malaysia. However, certain tribes have also engaged in various commercial economic endeavours, like the production of durian, rubber, cacao, and palm oil. The Orang Asli community generally views these economic activities as a new opportunity to improve their standard of living and income stream. Unfortunately, many of them are incapable of transforming their tanah saka (customary land) to more productive and organized agriculture that could potentially be commercial due to many limitations, particularly those associated with property ownership not being officially recognized in Malaysia. Accordingly, this study aims to develop economic empowerment plans that can be effectively executed through the gazetting of the Orang Asli’s tanah saka. This study uses a qualitative method by applying an ethnographic approach through fieldwork at 14 Posts of the Temiar community in Gua Musang, Kelantan. The results of this study show that there are several potential economic empowerment plans that can be implemented if the land gazetting proposal is approved. Among the economic empowerment opportunities are the development of organised settlements, economic development of subsistence agriculture, commercial economic development, entrepreneurship development, rural tourism, guidance and training. In order to safeguard the well-being of the Orang Asli in Malaysia, especially the Temiar tribe, gazetting tanah saka (customary land) is crucial to the implementation of the RMK12 plan.